Effects of suspended particulate matter, surface oil layer thickness and surfactants on the formation and transport of oil-sediment aggregates (OSA). (April 2020) - Li, Haoshuai; Bao, Mutai; Li, Yang; Zhao, Lanmei; King, Thomas; Xie, Ying
Abstract: This study illustrated the significant effects of oil surface layer thickness, the presence of suspended particulate matter (i.e. sediment resuspension) and surfactants (chemical oil dispersants and a bio-surfactant) on the formation and transport of oil-sediment aggregates (OSA). Oil spill thickness on surface waters influenced the weathering rates of residual oil. Thin oil slicks on the water surface were more readily dispersed by physical processes. This study provided evidence for the dispersion of thin oil slicks by the bursting of air bubbles. The OSA formation within the water column by interaction of oil with suspended particulate materials promoted the sedimentation of oil. The addition of a chemical dispersant (i.e., GM-2) and biosurfactant (i.e., rhamnolipid) to a surface oil slick increased the dissolved and aggregated oil concentrations in the aqueous phase and subsequent oil biodegradation rates. These findings provide a deeper understanding on the processes influencing vertical distribution and environmental persistence of a crude oil spilled on the ocean surface both in the presence and absence of surfactant additions. Graphical abstract: Image 1 Highlights: Sediment resuspension impact oil weathering and transport to both the water and sediment phases. This study provided evidence for the dispersion of thin oil slicks by the bursting of air bubbles. The OSA formation within the water column promoted the sedimentation of oil. The chemical dispersant and biosurfactant increased subsequent oil biodegradation rates.